Microstructure, Microhardness, and Wear Properties of Cobalt Alloy Electrodes Coated with TiO2 Nanoparticles - Sebastian Balos; Petar Janjatovic; Miroslav Dramicanin; Danka Labus Zlatanovic; Branka Pilic; Pavel Hanus; Lucyna Jaworska (Metals, 2019)
In this paper, the influence of TiO2 nanoparticle coating on cobalt-based electrodes was studied. Different coating treatment times were applied, and the results were compared to the hard-faced layer obtained with unmodified electrodes. The hard facing was done in three layers, the first being a Ni-based interlayer, followed by two layers of corrosion and wear-resistant Co-based Stellite 6 alloy. Pin-on-disc wear testing was applied, along with the metallographic study and hardness measurements of the hard-faced layers. Furthermore, energy-dispersive X-ray spectroscopy (EDS) analysis was conducted. It was found that the microstructural properties, as well as microhardness profiles, are modified in hard-faced layers obtained with modified electrodes. Interdendritic distances are altered, as are the dendrite growth directions. Titanium oxides are formed, which, along with the present complex carbides, increase the wear resistance of the hard-faced layers compared to layers obtained with untreated electrodes.